2019
DOI: 10.1007/978-3-030-24258-9_15
|View full text |Cite
|
Sign up to set email alerts
|

On Computing the Union of MUSes

Abstract: This paper considers unsatisfiable CNF formulas and addresses the problem of computing the union of the clauses included in some minimally unsatisfiable subformula (MUS). The union of MUSes represents a useful notion in infeasibility analysis since it summarizes all the causes for the unsatisfiability of a given formula. The paper proposes a novel algorithm for this problem, developing a refined recursive enumeration of MUSes based on powerful pruning techniques. Experimental results indicate the practical sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The computation of the union UMUS F has been examined in two recent studies [13,45] that provided two different approaches for that task. Unfortunately, due to the problem's hardness, both the studies showed that the proposed approaches can usually handle only relatively small input formulas.…”
Section: W 3 -The Union Of Musesmentioning
confidence: 99%
See 1 more Smart Citation
“…The computation of the union UMUS F has been examined in two recent studies [13,45] that provided two different approaches for that task. Unfortunately, due to the problem's hardness, both the studies showed that the proposed approaches can usually handle only relatively small input formulas.…”
Section: W 3 -The Union Of Musesmentioning
confidence: 99%
“…While the early applications relied on identifying a single [3,6,7,51,53] or enumerating multiple [4,10,12,39,41,52] MUSes, the rapid adoption of MUSes lead researchers to investigate problem formulations and their corresponding applications that do not rely on explicit MUS identification. These include, e.g., computing the union of all MUSes [45], deciding whether a given clause belongs to an MUS [31], or counting the number of MUSes. Especially, the counting of MUSes found many applications in the domain of diagnosis where the MUS count can be used to compute various inconsistency metrics [25,29,[48][49][50]65] for general propositional knowledge bases.…”
Section: Introductionmentioning
confidence: 99%
“…The MUS-union problem was recently investigated by Mencia et al [ 42 ]. Their algorithm is based on gradually refining an under -approximation of until the exact is computed.…”
Section: Related Workmentioning
confidence: 99%
“…Luo et al [19] proposed a method for accelerating the enumeration of MUSes based on inconsistency graph partitioning. A novel algorithm [20] is presented for computing the union of the clauses included in some MUSes, by developing a refined recursive enumeration of MUSes based on powerful pruning techniques.…”
Section: Algorithms Of Extracting Unsatisfiable Subformulamentioning
confidence: 99%